Bibliometric Analysis of Work Envinronment and Employee Job Satisfaction - Judijanto, Loso (Eastasouth Institute, 2025)
This study presents a comprehensive bibliometric analysis of the global research landscape on the relationship between work environment and employee job satisfaction. Using data retrieved from the Scopus database and analyzed with VOSviewer (version 1.6.x), the study maps publication trends, influential authors, collaborative networks, and thematic clusters spanning the years 2000–2024. The co-authorship analysis identifies prominent contributors such as Bakker A.B. and Judge T.A., while the country collaboration map reveals the dominance of the United States and the growing participation of countries like India, China, and Malaysia. Keyword co-occurrence analysis shows a conceptual structure centered on themes such as occupational health, job stress, leadership, and employee well-being, with “job satisfaction” and “work environment” as central nodes. Temporal and density visualizations suggest an increasing emphasis on holistic constructs such as work-life balance, mental health, and quality of life. The findings underscore the interdisciplinary and evolving nature of this field, offering guidance for future research directions and practical implications for organizational policy and human resource management.